2019
DOI: 10.3389/fphys.2019.01351
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin: Novel Treatment in Neonatal Hypoxic-Ischemic Brain Injury

Abstract: Hypoxic-ischemic encephalopathy (HIE) is a major cause of mortality and morbidity in neonates, with an estimated global incidence of 3/1,000 live births. HIE brain damage is associated with an inflammatory response and oxidative stress, resulting in the activation of cell death pathways. At present, therapeutic hypothermia is the only clinically approved treatment available for HIE. This approach, however, is only partially effective. Therefore, there is an unmet clinical need for the development of novel ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 84 publications
(127 reference statements)
1
15
0
Order By: Relevance
“…Accordingly, in the study of Ferreira et al, the authors found a dose-dependent neuroprotection provided by immediate and delayed treatment with Cur following neonatal hypoxic-ischemic brain injury. The precise mechanism of this protection is unclear; however, their results showed effects of Cur on oxidative stress and myelination, inflammation and transcription (STAT3 Y705) and mitochondrial dysfunction (STAT3 S727 and PHB) [ 55 ]. Considering this, cells cultured under hypoxic conditions can be used as a valid in vitro model in order to evaluate the anti-ROS properties of active molecules such as Cur.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, in the study of Ferreira et al, the authors found a dose-dependent neuroprotection provided by immediate and delayed treatment with Cur following neonatal hypoxic-ischemic brain injury. The precise mechanism of this protection is unclear; however, their results showed effects of Cur on oxidative stress and myelination, inflammation and transcription (STAT3 Y705) and mitochondrial dysfunction (STAT3 S727 and PHB) [ 55 ]. Considering this, cells cultured under hypoxic conditions can be used as a valid in vitro model in order to evaluate the anti-ROS properties of active molecules such as Cur.…”
Section: Resultsmentioning
confidence: 99%
“…Curcumin possesses several beneficial properties that could make it a suitable candidate for stroke prevention or treatment, including anti-inflammatory, antilipemic, antiaggregant, neuroprotective and epigenetic modulatory activities [ 275 ]. Pre- and posthypoxia treatment with curcumin was found to effectively promote neuroprotection in rat neurons challenged with OGD [ 276 ], in neonatal mice subjected to hypoxic–ischemic brain injury [ 277 ], in MCAO rodents [ 278 , 279 , 280 , 281 , 282 , 283 , 284 ] and in stroke-prone spontaneously hypertensive rats [ 285 ].…”
Section: Polyphenols and Stroke: Results From Preclinical Stroke Mmentioning
confidence: 99%
“…Also, curcumin inhibits the expression of pro-inflammatory cytokines (IL-1, IL-6, and TNF-α), thus mediating inflammation and inhibiting STAT3 phosphorylation ( Maheshwari et al, 2006 ; Alexandrow et al, 2012 ). Recently, our group demonstrated that curcumin provides dose-dependent neuroprotection through immediate and delayed application following neonatal HI ( Rocha-Ferreira et al, 2019 ). Two hundred micrograms per gram BW of curcumin reduced tissue loss, microglial and astroglial activation, and cell death after HI injury in a P7 mouse model.…”
Section: Experimental Hi Treatmentsmentioning
confidence: 99%
“…Prohibitin (PHB) is a protein considered essential in regulating mitochondrial structure and acting as a chaperone for the respiratory chain proteins. Curcumin administration post-HI increased PHB protein levels and provided neuroprotection through prevention of mitochondrial dysfunction during secondary energy failure ( Rocha-Ferreira et al, 2019 ). Additionally, in a study conducted by Cui et al (2017) , curcumin was administrated to P7 rats at a dose of 150 mg/kg per day for 3 days, 24 h after induced HI-injury and resulted in prevention of myelin loss ( Cui et al, 2017 ).…”
Section: Experimental Hi Treatmentsmentioning
confidence: 99%